2020
DOI: 10.1111/ina.12755
|View full text |Cite
|
Sign up to set email alerts
|

Decreased humidity improves cognitive performance at extreme high indoor temperature

Abstract: With the significant rise and frequent occurrence of outdoor temperature and humidity during the summer, the indoor temperature and humidity also showed similar trends in the subtropical hot-humid regions. A field study at Chongqing University in China showed that the range of temperature and relative humidity in classroom was, respec-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(21 citation statements)
references
References 51 publications
(124 reference statements)
3
17
0
1
Order By: Relevance
“…This result is consistent with the studies by Vasmatzidis et al and Trezza et al, which found that the memory function of people acutely exposed to high humidity is significantly lower than that of people exposed to low humidity [33,34]. In addition to memory function, some studies have found that a high relative humidity (70%) environment (e.g., subtropical climate) can reduce the cognitive ability of individuals [35], such as psychomotor speed and visual learning [33,35], making it more difficult for them to think clearly and reducing their alertness [36]. This may be due to the influence of relative humidity on the body's of 14 ability of thermal sensation and thermoregulation.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This result is consistent with the studies by Vasmatzidis et al and Trezza et al, which found that the memory function of people acutely exposed to high humidity is significantly lower than that of people exposed to low humidity [33,34]. In addition to memory function, some studies have found that a high relative humidity (70%) environment (e.g., subtropical climate) can reduce the cognitive ability of individuals [35], such as psychomotor speed and visual learning [33,35], making it more difficult for them to think clearly and reducing their alertness [36]. This may be due to the influence of relative humidity on the body's of 14 ability of thermal sensation and thermoregulation.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, high humidity conditions are more likely to cause pollution of atmospheric particles [50]. In addition, because of the urban heat island effect, a large number of studies have shown that in a high-heat and high-humidity environment, human cognitive function will be significantly reduced [34,35,51].…”
Section: Discussionmentioning
confidence: 99%
“…In recent research, Mohamed et al (2021) discovered that classroom temperature influenced academic performance. These findings coincide with Tian et al (2021). This is because the authors discovered that cold and hot surroundings severely impact pupils' academic performance compared to thermally neutral conditions.…”
Section: Discussionsupporting
confidence: 69%
“…The list of potential covariates included age in years, sex (women or men), BMI in kg/m 2 , educational level (below elementary school, elementary school, middle and high school, college and above), marital status (married, separated or divorced, widowed, others (e.g., single, living together)), geographical region (Ansan or Ansung), physical activity (yes or no as to whether the study participants regularly exercise to make their bodies sweat at least once a week), smoking (never, former, current), alcohol consumption (never, former, moderate, heavy), diabetes mellitus (yes or no), hypertension (yes or no), hyperlipidemia (yes or no), cerebrovascular disease (yes or no), prior diagnosis of cancer (yes or no), relative temperature in °C, relative humidity in %, and season of participants’ study visit. We included relative temperature and humidity, as well as the season of the study visit, based on their relationship with PM concentrations documented in the literature [ 19 , 20 ].…”
Section: Methodsmentioning
confidence: 99%